La redécouverte des décors du théâtre de la maison de George Sand à Nohant - Marie-Noëlle Laurent-Miri; Julie Barth; Élisabeth Portet (In Situ)
George Sand’s house at Nohant has a theatre of remarkable authenticity. Most of its ornaments and accessories of the period have been preserved, including a unique collection of painted stage sets made for George Sand for her own entertainment and that of her guests. This private theatre was installed on the ground floor of the house between 1849 and 1857 and belongs to a tradition of ‘society’ theatres constructed according to the Italian model with a tall proscenium arch to accommodate movable sets giving an impression of perspective. Although this theatre at Nohant is on a relatively small scale, it nonetheless has all the design features necessary to stage a proper play, with wings for the circulation of the actors, lighting equipment and devices for sound effects. The conservation of the collection of painted stage sets was the point of departure for a restoration project that drew up an inventory and examined the possibilities of using the sets anew in theatrical productions. The analysis of the collection revealed two distinct ensembles, one of them showing a greenhouse, with highly original iconography. The restoration of the theatre with the insertion of a new lighting system and a change of décor allowing for the greenhouse ensemble to be installed was carried out in 2021. This was an exceptional undertaking both in terms of the preparation of the conservation and restoration of the sets and the coordination of an interdisciplinary team of nine restorers. It became possible to establish connections between the material understanding of the collection, through the precise study of the way its use had left traces on it, and the history of daily life at Nohant in George Sand’s time. The article presents the objectives and main stages in the restoration project. It pays particular attention to the theatre’s specificities and to the discoveries made during the operation, in particular the play performed in the new décor.